Social Responsibility According to Imam Al-Juwaini in his Book “Ghiyath al-Umam Fi Al-Thiath Al-Zulm”: A Fundamental Study - Abed, Falah; Al-Khafaji, Sarhan; Hasan, Marwah (Dirasat: Human and Social Sciences, 2022)
The study intends to identify both the geomorphologic and hydrological characteristics of Lake Sawa regarding its water sources and the specific attributes of this water. The study focused on the impact of climate on lake surface water's physical and chemical properties. The analysis of both the data for a major climate cycle (30 years) for the period (1989- 2018) and the samples taken from Lake Sawa water depth (1-5) meters proved that the climate had changed the physical and chemical properties of lake water; besides, the extensive evaporation of its water and the lack of rain precipitation in the lake raised salts ratio to 22885 (mg/liter), as well as the rates of other physical and chemical elements.